(3JShjb GdNOeGJ GdeUQajI (B/s - (3hRGfj, eMeOs; (3RbGj, MejOjs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2021)
(3JShjb GdNOeGJ JWhQ eagheg heLGdGJ JWHjbg, eY CgejJg hefGaYg, cPdc eONd dJShjb GdNOeGJ GdeUQajI hGdHjFI GdJShjbjI ddeUGQa, hGdeRjL GdJShjbj GdeUQbj, HGdGVGaI Gdi ebOeI aj Sdhc GdeSJgdc GdeUQaj, hGdYhGed GdeMOOI dg eY JMbjb QVG GdYejd GdeUQajef NdGd LhOI GdNOeGJ GdeUQajI(B.s
(3eQGLY U(B.187194s
Keywords: (3GdNOeGJ GdeUQajI(B- (3JShjbs